Relationship between middle hitter and setter's position and its influence on the attack zone in elite men's volleyball - Peiro, M. I.; Parra, M.; Leon, J.; Fradua, L.; Benitez, J. M.; Urena, A. (International Journal of Performance Analysis in Sport, 2016)
The purpose of this study was to determine whether the distance between the setter, the middle hitter and the second tempo attacker can predict the attack zone in Complex I in elite male volleyball. A total amount of 3,936 rallies corresponding to 23 matches of the Men's World Championship 2010 were analysed following a category system, recurring to an observational methodology. Measured variables were Availability of the middle hitter, Attack type, Latitude of the middle hitter, setter, and second tempo attacker, Second tempo attack lane and Distance between players